Scaling the Peaks Research Protocol: understanding the barriers and drivers to providing and using dementia friendly community services in rural areas: a mixed methods study - Marshall, Fiona; Basiri, Anahid; Riley, Mark; Dening, Tom; Gladman, John R.F.; Griffiths, Amanda; Lewis, Sarah (BMJ Publishing Group Ltd, 2018)
Introduction: Scaling the Peaks is a cross-disciplinary research study which draws on medical ethnography, human geography and Geospatial Information Science (GIS) to address the issues surrounding the design and delivery of dementia friendly services in rural communities. The research question seeks to understand the barriers and drivers to the development of relevant, robust, reliable and accessible services which make a difference among older rural families affected by dementia. Methods and analysis: This mixed methods study recruits both families affected by dementia who reside within the Peak District National Park, Derbyshire, and their service providers. The study explores the expectations and experiences of rural dementia by adopting a three part approach: (1) longitudinal ethnographic enquiry with up to 32 families affected by dementia (aged 70 years plus) who identify themselves as rural residents; (2) ethnographic semi-structured interviews and systematic observations of a range of statutory, third sector, private and local community initiative’s which seek to support older people living with dementia; (3) geospatial visual mapping of the qualitative and quantitative data. The ethnographic data will be used to explore the ideas of belonging in a community, perceptions of place and identity to determine the factors which influence everyday decisions about living well with dementia and, for the providers, working in a rural community. The geospatial component of the study seeks to incorporate quantitative and qualitative data, such as types, locations and allocation of services to produce an interactive web-based map for local communities to determine the future design and delivery of services when considering dementia friendly services. Ethics and dissemination: The study is approved by the Leeds and Humberside Health Research Authority 16/YH/0163. The study is also approved by other participating organisations as required by their own governance procedures. The study includes people with dementia and as such adheres to the ethical considerations when including people with dementia. A publically available interactive visual map of the findings will be produced in relation to current services related to location and, by default, identify gaps in provision. Formal reports and dissemination activities will be undertaken in collaboration with the study advisory group members.